Changes in Global Left Ventricular Myocardial Work Indices and Stunning Detection 3 Months After ST-Segment Elevation Myocardial Infarction - Lustosa Rodolfo P.; Fortuni Federico; van der Bijl Pieter; Mahdiui Mohamed El.; Montero-Cabezas Jose M.; Kostyukevich Marina V.; Knuuti Juhani; Marsan Nina A.; Delgado Victoria; Bax Jeroen J. (Elsevier Inc., 2022)
Global left ventricular (LV) myocardial work (MW) indices (GLVMWI) are derived from speckle tracking echocardiographic strain data in combination with non-invasive blood pressure measurements. Changes in global work index (GWI), global constructive work (GCW), global wasted work (GWW) and global work efficiency (GWE) after ST-segment elevation myocardial infarction (STEMI) have not been explored. The aim of present study was to assess the evolution of GLVMWI in STEMI patients from baseline (index infarct) to 3 months’ follow-up. Three-hundred and fifty patients (265 men; mean age 61 ± 10 years) with STEMI treated with primary percutaneous coronary intervention (PCI) and guideline-based medical therapy were retrospectively evaluated. Clinical variables, conventional echocardiographic measures and GLVMWI were recorded at baseline within 48 hours post-primary PCI and 3 months’ follow-up. LV ejection fraction (from 54 ± 10% to 57 ± 10%, p < 0.001), GWI (from 1449 ± 451 mm Hg% to 1953 ± 492 mm Hg%, p < 0.001), GCW (from 1624 ± 519 mm Hg% to 2228 ± 563 mm Hg%, p < 0.001) and GWE (from 93% (interquartile range (IQR) 86%-95%) to 95% (IQR 91%-96%), p < 0.001) improved significantly at 3 months’ follow-up with no significant difference in GWW (from 101 mm Hg% (IQR 63-155 mm Hg%) to 96 mm Hg% (IQR 64-155 mm Hg%); p = 0.535). On multivariable linear regression analysis, lower values of troponin T at baseline, increase in systolic blood pressure and improvement in LV global longitudinal strain were independently associated with higher GWI and GCW at 3 months’ follow-up. In conclusion, the evolution of GWI, GCW and GWE in STEMI patients may reflect myocardial stunning, whereas the stability in GWW may reflect permanent myocardial damage and the development of non-viable scar tissue.